The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1016/j.bpj.2014.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Dual Biochemical Oscillators May Control Cellular Reversals in Myxococcus xanthus

Abstract: Myxococcus xanthus is a Gram-negative, soil-dwelling bacterium that glides on surfaces, reversing direction approximately once every 6 min. Motility in M. xanthus is governed by the Che-like Frz pathway and the Ras-like Mgl pathway, which together cause the cell to oscillate back and forth. Previously, Igoshin et al. (2004) suggested that the cellular oscillations are caused by cyclic changes in concentration of active Frz proteins that govern motility. In this study, we present a computational model that inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…On a molecular level, cell reversals are triggered by a pole-to-pole change in motility proteins, such as FrzZ, MglB and MglA, which then causes the Myx. xanthus cell to reverse direction (Eckhert et al, 2014;Kaimer & Zusman, 2013;Keilberg & Søgaard-Andersen, 2014). …”
Section: Rippling Behaviourmentioning
confidence: 99%
“…On a molecular level, cell reversals are triggered by a pole-to-pole change in motility proteins, such as FrzZ, MglB and MglA, which then causes the Myx. xanthus cell to reverse direction (Eckhert et al, 2014;Kaimer & Zusman, 2013;Keilberg & Søgaard-Andersen, 2014). …”
Section: Rippling Behaviourmentioning
confidence: 99%
“…Cells may gain some control of their movements by breaking free of this rigid oscillation. A model that might explain how this could occur exploits the similarity between the chemotactic signal transduction (Che) system that controls the direction of rotation of the bacterial flagellar motor and the Frz signaling system in myxobacteria that controls cell reversal frequency [28]. …”
Section: Motor Complexes and Traffic-jamsmentioning
confidence: 99%
“…xanthus changes its direction of movement by swapping the leading and lagging poles. The reversal frequency is regulated by the chemosensory-like frizzy (Frz) pathway, which relays environmental signals to the downstream MglA-MglB polarity control system [1113] (Fig 1). High-resolution time-lapse experiments revealed that MglA and MglB relocalize sequentially during a reversal [4,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that RomR and its interacting partner RomX are essential for recruiting MglA-GTP to the poles [16]. Frz-signaling and RomR stimulates the pole-to-pole exchange of MglA and MglB [11,1315]. All together, these proteins form a so-called gated relaxation oscillator, which functions to drive the polarity reversals in response to environmental signals [11].…”
Section: Introductionmentioning
confidence: 99%